2012
DOI: 10.1371/journal.pone.0043381
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Chicken Thrombocyte Responses to Toll-Like Receptor Ligands

Abstract: Thrombocytes are the avian equivalent to mammalian platelets. In addition to their hemostatic effects, mammalian platelets rely in part on pattern recognition receptors, such as the Toll-like receptors (TLR), to detect the presence of pathogens and signal the release of certain cytokines. Ligands for TLRs include lipopolysaccharide (LPS), which is bound by TLR4, as well as unmethylated CpG DNA motifs, which are bound by TLR9 in mammals and TLR21 in chickens. Similar to mammalian platelets, avian thrombocytes h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
35
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(41 citation statements)
references
References 35 publications
6
35
0
Order By: Relevance
“…These results are similar to responses from avian macrophages treated with the same class of CpG-ODN or LPS (Haddadi et al, 2013). In contrast, avian thrombocytes showed significant up-regulation of IFN-␣, but marginal increase in IFN-␤ transcripts after high dose LPS or low dose CpG-ODN treatment (St Paul et al, 2012a). The lack of type I IFN responses may be related to the class of CpG-ODN used, as generally class A CpG-ODN robustly induce IFN-␣ compared to class B CpG-ODN, at least in mammals (Krug et al, 2001).…”
Section: Induction Of Irfs and Type I Ifnssupporting
confidence: 76%
See 1 more Smart Citation
“…These results are similar to responses from avian macrophages treated with the same class of CpG-ODN or LPS (Haddadi et al, 2013). In contrast, avian thrombocytes showed significant up-regulation of IFN-␣, but marginal increase in IFN-␤ transcripts after high dose LPS or low dose CpG-ODN treatment (St Paul et al, 2012a). The lack of type I IFN responses may be related to the class of CpG-ODN used, as generally class A CpG-ODN robustly induce IFN-␣ compared to class B CpG-ODN, at least in mammals (Krug et al, 2001).…”
Section: Induction Of Irfs and Type I Ifnssupporting
confidence: 76%
“…Recent TLR expression profiling studies in chickens have revealed that certain TLRs are expressed not only in the classical innate immune system cells, but also in thrombocytes (St Paul et al, 2012a) and various adaptive immune system cells, such as B cells (St Paul et al, 2012b). As a consequence of TLR-PAMP interactions, cells undergo changes in expression of an array of antiviral substances, such as type I and II interferons (IFNs) (St Paul et al, 2012b).…”
Section: Introductionmentioning
confidence: 99%
“…Our functional assessment of the phagocytic responses of thrombocytes complements recent molecular analyses, which showed that thrombocytes express genes involved in antigen presentation and the inflammatory response (40, 41). The functional significance and evolutionary implications of the phagocytic thrombocytes are discussed in relation with the immune functions of mammalian platelets.…”
Section: Introductionsupporting
confidence: 61%
“…Peak responses of chicken thrombocytes have been reported with high doses of LPS and CpG [29], but a low dose of LPS induces higher nitric oxide production in chicken macrophages [16]. Moreover, the dose of TLR2 ligands can affect chicken splenocyte responses [30].…”
Section: Discussionmentioning
confidence: 99%